Imbalance in Life Table: Effect of Infant Mortality on Lower Life Expectancy at Birth - Fazle Rabbi, A. M. (Journal of Scientific Research, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Life expectancy at birth is a well-known demographic measure of population longevity. Rationally, life expectancy at birth should be higher than life expectancy at any particular age. However, historically, lower life expectancy at birth is observed than that of age one, which diminishes the feature of life expectancy at birth as a prominent indicator of longevity. High infant and child mortality rates result in lower values of life expectancy at birth than at older ages. This imbalance in life table disappears only when the crossover occurs and it happens when the inverse of the infant mortality becomes equal to the life expectancy at age one. For Matlab Health and Demographic surveillance system of Bangladesh, life expectancy at age one is still higher than life expectancy at birth. Required infant mortality rate to achieve crossover suggests further decline in infant mortality for Matlab HDSS to attain crossover of life expectancy at birth and age one. Keywords: Life expectancies; Developing countries; Imbalance; Life table. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i3.14105 J. Sci. Res. 5 (3), 479-488 (2013)